Is Autogenous cortical bone sheet reliable for the management of defects around dental implants by using scalpel technique? - Burak Bayram (Selçuk University, 2020)
Background: The aim of this study is to present a very easy technique for coverage of dehiscence and fenestration defects around the dental implantsfrom the nearest bone source by using a sharp scalpel and the analysis of its clinical results.Materials and Methods:750 screw dental implants were inserted by the same surgeon. Exactly 112 of the (15%) implants had dehiscence defects and 23 of them (3 %) had fenestration defects. A bone sheet was obtained from the nearest available cortical bone for covering a bone defect around an implant by using a new no: 15 scalpel. Survival rates of implants were evaluated.Results:One hundred and thirty-five exposed implant surfaces were augmented with autogenous bone, harvested by scalpel technique. The survival rate of these implants was 100% with no significant clinical finding.Conclusion:The scalpel technique described in the present study is easy, effective and reliable for the management of dehiscence or fenestration defects of dental implants.Key words: Autogenous bone grafting, defects around dental implants, dental implants